Obelists at sea - King, C. Daly, 1895-1963 (Otto Penzler's classic American mystery library., 2023)
"C. Daly King's debut mystery is a tale of murder, travel, and psychiatry set aboard a luxury transatlantic liner. The smoking room on a transatlantic cruise ship is bound to be a hotbed of activity--but it's less common for it to be the site of a murder. Yet, when the lights flicker aboard the luxury Meganaut, making its way from New York to Paris, this is precisely what happens; in the darkness, a gunshot rings out, and when the light is restored, a man is found dead. The situation becomes all the more curious when it's discovered that the deceased had apparently ingested cyanide just seconds before being penetrated by the bullet. Luckily, for the other passengers, there are two detectives aboard the Meganaut, ready to leap into action. There are also four psychiatrists, and those psychiatrists convince the captain to let them take a stab at solving the crime, using their professional understanding of the human psyche to determine who could have been capable of such a crime--and why. But will they be able to deduce the puzzle's solution before the killer strikes again? The first of seven novels by psychologist C. Daly King, Obelists at Sea is intelligent and enjoyable Golden Age mystery fare, featuring an atmospheric setting, carefully placed clues, and a complex whodunnit plot explained with sharp-witted ratiocination"--